Poverty Profile of the Philippines - Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2000)
Poverty incidence has been declining in the Philippines over the past 10 years. However, with the advent of the Asian crisis in 1997, there was a reversal in poverty trends. Estimates indicate that the headcount index has gone up to 40 percent in 1998 from 31.8 percent in 1997. Other nonincome-based measures of poverty also suggest deterioration in the welfare conditions, particularly of the poor.The paper looks at the trends in the Philippines in the past ten years using income-based and nonincome-based measures of poverty. In particular, indicators relating to employment, education, health and access to basic facilities are used.
Keywords: 330; poverty alleviation; poverty incidence; poverty